Layout Optimization of Microsatellite Components Using Genetic Algorithm - Mohammad Mukhayadi; Irman Hermadi; Soewarto Hardhienata (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
The placement of satellite components usually belongs to non-deterministic polynomial-time hard (NP-hard) problems that in terms of computational complexity is very difficult to solve. This problem is normally known as layout optimization problem (LOP). In this study the layout of microsatellite components has to meet the requirements set by mission payloads, launcher and spacecraft attitude control. The novel scheme is to find the various possibilities of optimal layout using genetic algorithms combined with order-based positioning technique (OPT). Each component has a given index and then placed in a container based on specific order of placements in accordance with a bottom-left (BL) algorithm that is already established. The placement order is generated by the genetic algorithm which explore various possibilities to obtain a sequence that brings the best solution.